Evolution of chest CT manifestations of COVID-19: a longitudinal study - Kong, Min (J Thorac Dis, 2020)
BACKGROUND: The aim of this study was to investigate the chest CT manifestations of COVID-19 and its CT evolving process to explore its inherent outcomes. METHODS: Inpatients diagnosed with COVID-19 at the Enze Hospital from January 17, 2020 to February 15, 2020 were included. The evolving characteristics of CT manifestations and treatment outcomes were analyzed. RESULTS: Twenty-two patients with COVID-19 were included in the study. Clinical symptoms at the time of onset included fever (n=19) and cough (n=8). The first CT findings mainly included ground-glass opacities (GGOs) (n=18), lung consolidation (n=7), interlobular septal thickening (n=5), and fibrosis-like stripes (n=4). Dynamic CT showed GGOs, lung consolidation, and fibrosis-like stripes, all of which demonstrated a trend that initially increased in number, and then gradually decreased in number or disappeared. According to the characteristics of CT evolution. COVID-19 could be divided into early stage, progressing stage, recovery stage, and dissipation stage. The median times of the respective stages were: early stage—3 days (1–8 days) after disease onset, progressing stage—7 days (4–17 days) after onset, recovery stage—10 days (8–14 days) after onset, and dissipation stage—19.5 days (11–25 days) after onset. CONCLUSIONS: COVID-19 has an acute onset, with main imaging manifestations of different types of GGO with or without lung consolidation in the subpleural regions of the bilateral lungs. The CT manifestations of lung lesions change rapidly. The lung lesions of mild and ordinary types of COVID-19 may improve significantly or disappear in a short period after active treatment, with good prognosis. Moreover, fibrosis-like stripes may be a sign of atelectasis of sub-segment lung tissue of COVID-19 and may be a specific sign for the diagnosis of COVID-19.